Effects of simvastatin only or in combination with continuous combined hormone replacement therapy on serum lipid levels in hypercholesterolaemic post-menopausal women - FAK, ALİ SERDAR (OXFORD UNIV PRESS, 2000)
Aims To evaluate the effects of simvastatin only or combined with continuous hormone replacement therapy on the serum lipid profile in hypercholesterolaemic post-menopausal women. Methods and Results One hundred hypercholesterolaemic post-menopausal women were given either simvastatin 10 mg daily together with oestrogen 0.625 mg and medroxyprogesterone 2.5 mg daily (HRT + simvastatin group) (n:50) or simvastatin 10 mg daily (simvastatin only group) (n:50) in a prospective manner. Serum total, low density lipoprotein, and high density lipoprotein cholesterol and triglyceride levels were measured at baseline, at 3 and 6 months. The initial mean (+/- SD) cholesterol values were as follows for the HRT + simvastatin group and the simvastatin only group, respectively: total cholesterol 240.0 +/- 28.0 and 248.9 +/- 28.2 mg . dl(-1) ; low density lipoprotein cholesterol 174.7 +/- 25.6 and 175.1 +/- 25.9 mg . dl(-1); high density lipoprotein cholesterol 37.2 +/- 5.0 and 39.9 +/- 7.3 mg . dl(-1) Compared with the baseline, total and low density lipoprotein cholesterol levels decreased; and high density lipoprotein cholesterol levels increased significantly at 3 and 6 months in both groups. However, the mean percent reduction in total cholesterol and low density lipoprotein cholesterol was significantly greater in the HRT + simvastatin group compared with the simvastatin only group both at 3 months (12.3 +/- 7.0% vs 8.9 +/- 6.2%; P < 0.01; and 19.0 +/- 10.6% vs 13.2 +/- 10.4%; P < 0.005, respectively) and at 6 months (14.6 +/- 7.7% vs 11.3 +/- 7.4%; P < 0.05 and 23.3 +/- 9.7% vs 15.8 +/- 12.3%; P < 0.005, respectively). The mean percent increase in serum high density lipoprotein cholesterol concentrations was also significantly greater in the HRT + simvastatin group compared with the simvastatin only group at both times (14.6 +/- 11.8% vs 9.8 +/- 11.8%; P < 0.005, at 3 months, and 21.3 +/- 15.2% vs 11.1 +/- 12.5; P < 0.005, at 6 months, respectively). Furthermore, significantly more patients in the HRT + simvastatin group than in the simvastatin only group attained their target treatment goals dictated by the National Cholesterol Education Program Adult Treatment Panel II Guidelines. Although the mean percent decrease in triglyceride levels was significantly greater in the HRT + simvastatin group at 3 months, the significance disappeared at 6 months. Conclusion The combination of simvastatin and continuous combined hormone replacement therapy seems to be more effective than simvastatin only in the treatment of hypercholesterolaemia in post-menopausal women. (C) 2000 The European Society of Cardiology.
Keywords: simvastatin; hormone replacement therapy; oestrogen; progesterone; hypercholesterolaemia; CORONARY HEART-DISEASE; POSTMENOPAUSAL WOMEN; ESTROGEN REPLACEMENT; LIPOPROTEIN CHOLESTEROL; ARTERY DISEASE; PLASMA; HEALTH